Guided Inquiry Assisted by E-Module Socio Scientific Issues Integrated Islamic Values in the Earth and Solar System Material: Its Impact on Improving Students' Scientific Argumentation skills - Niki Dian Permana P; Annisa Syafira; Diniya Diniya; Zarkasih Zarkasih; Faruku Aliyu (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to determine the improvement in students' scientific argumentation skills through the application of the E-Module Socio scientific issues (SSI) Based on Islamic Values integrated with the Guided Inquiry learning model in Earth and Solar System lessons. A true experimental method was used in this study with a pretest-posttest control group design. All 255 students of class VII at one of the Madrasah Tsanawiyah (MTs) in Pekanbaru were the population of this study. Random sampling technique was used in this research, and the samples selected were 32 the seventh-grade students of class A as the experimental group taught by implementing Islamic Values integrated E-Module SSI assisted Guided Inquiry learning model and 33 students of class C as the control group taught by implementing conventional learning model. Collecting data was done by giving pretest and posttest to find out the increase of student scientific argumentation skills. The test data were analyzed by using independent sample t-test. The statistical test results with the assistance of SPSS 20 showed that the significant score 0.000 was lower than 0.05, so Ha was accepted and H0 was rejected. It meant that there was a significant difference of scientific argumentation skill increase between students taught by implementing Islamic Values integrated E-Module SSI assisted Guided Inquiry learning model and those who were taught by implementing conventional learning model on Earth and Solar System lesson at the seventh-grade of Madrasah Tsanawiyah.Keywords: Guided Inquiry; Scientific Argumentation Skills; S0cio Scientific Issues; E-Module; Islamic Values